Forecasting metal prices: Do forecasters herd? - Christian Pierdzioch; Jan-Christoph Rülke; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2012)
We analyze more than 20,000 forecasts of nine metal prices at four different forecast horizons. We document that forecasts are heterogeneous and report that anti-herding appears to be a source of this heterogeneity. Forecaster anti-herding reflects strategic interactions among forecasters that foster incentives to scatter forecasts around a consensus forecast.
Keywords: G17; C33; L61; 330; Metal prices; Forecasting; Forecaster (anti-)herding